The Studies on Physico-chemical, Mineral, and Sensory properties of Sweet Potato Flour: A studies on phsico-chemical, functional and sensory properties of yellow flesh sweet potato flour - Afolabi, K. A.; Taiwo, K. A.; Morakinyo, T. A.; Badiora, O. A. (European Journal of Applied Sciences, 2021)
The physio-chemical, mineral, and sensory properties of sweet potato flour were studied. Sweet potato tubers were peeled, washed, diced into 1.5 and 10.0 mm thickness, blanched for 2 and 7 mins. Blanched and un-blanched samples were dried at 70 oC, milled, and packaged. The proximate composition, functional and nutritional properties as well as the sensory acceptability of the reconstituted product were determined. Results have shown that pH values ranged from 5.7-5.8, bulk density increased to 28% relative to the blanching time. Water absorption and oil absorption capacities were reduced with an increase in blanching time. Swelling capacity increased relatively to temperature but reduces as blanching time increased. The effect of blanching time on mineral content was insignificant, while flour of 10.0 mm samples thickness had higher values. The pasting temperature and peak viscosity range between 78.19-88.33 oC and 11.95-382.31 RUV, respectively. However, peak, trough, breakdown, setback, and final viscosities all reduced as blanching time increased and the 1.5 mm samples had higher values than the 10 mm samples. As blanching time and sample thickness increased the sensory attributes of reconstituted flour studied obtained lower scores. The color got darker and the un-blanched samples A and B were the most preferred. The sensory analysis of the reconstituted flour samples indicated that the un-blanched samples A and B were the most preferred samples. Conclusively, blanching for a long period is not suitable for the processing of sweet potato flour. Keyword: Sweet potatoes, physico-chemical properties, quality parameters, un-blanched, blanched, sweet potato flour.